Migration, integration and connectivity on the southeastern frontier of the Carolingian Empire - Džino, Danijel, 1971-; Milošević, Ante, 1953-; Vedriš, Trpimir, 1976- (Leiden : Brill, 2018)
The collection Migration, Integration and Connectivity on the Southeastern Frontier of the Carolingian Empire offers insights into the Carolingian southeastern frontier-zone from historical, art-historical and archaeological perspectives. Chapters in this volume discuss the significance of the early medieval period for scholarly and public discourses in the Western Balkans and Central Europe, and the transfer of knowledge between local scholarship and macro-narratives of Mediterranean and Western history. Other essays explore the ways local communities around the Adriatic (Istria, Dalmatia, Dalmatian hinterland, southern Pannonia) established and maintained social networks and integrated foreign cultural templates into their existing cultural habitus. Contributors are Mladen Ančić, Ivan Basić, Goran Bilogrivić, Neven Budak, Florin Curta, Danijel Dzino, Krešimir Filipec, Richard Hodges, Nikola Jakšić, Miljenko Jurković, Ante Milošević, Marko Petrak, Peter Štih, Trpimir Vedriš.
1, A View from the Carolingian Frontier Zone -- 2, From Byzantium to the West: "Croats and Carolingians" as a Paradigm-Change in the Research of Early Medieval Dalmatia -- 3, Carolingian Renaissance or Renaissance of the 9th Century on the Eastern Adriatic? -- 4, Migration or Transformation: The Roots of the Early Medieval Croatian Polity -- 5, The Products of the "Tetgis Style" from the Eastern Adriatic Hinterland -- 6, Carolingian Weapons and the Problem of Croat Migration and Ethnogenesis -- 7, Integration on the Fringes of the Frankish Empire: The case of the Carantanians and their neighbours -- 8, Istria under the Carolingian Rule -- 9, The Collapse and Integration into the Empire: Carolingian-Age Lower Pannonia in the Material Record -- 10, Imperium and Regnum in Gottschalk's Description of Dalmatia -- 11, Liber Methodius between the Byzantium and the West: Traces of the Oldest Slavonic Legal Collection in Medieval Croatia -- 12, The Installation of the Patron Saints of Zadar as a Result of Carolingian Adriatic Politics -- 13, Church, Churchyard, and Children in the Early Medieval Balkans: A Comparative Perspective -- 14, Trade and Culture Process at a 9th-Century Mediterranean Monastic Statelet: San Vincenzo al Volturno -- Afterword "Croats and Carolingians": Triumph of a New Historiographic Paradigm or Ideologically Charged Project?
Elektronická reprodukce.
Keywords: 8.-9. století; sociální změna -- Chorvatsko -- 8.-9. století; social change -- Croatia -- 8th-9th centuries; franská říše -- kulturní vztahy -- 8.-9. století; Jaderské moře (východní oblast) -- kulturní vztahy -- 8.-9. století; Frankish Empire -- cultural relations -- 8th-9th centuries; Adriatic Sea Eastern Region -- cultural relations -- 8th-9th centuries; e-knihy online; sborníky; studie; e-books online; papers of several authors; studies